2022
DOI: 10.21203/rs.3.rs-2341326/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple redox switches of the SARS-CoV-2 main protease in vitro provide new opportunities for drug design

Abstract: Besides vaccines, the development of antiviral drugs targeting SARS-CoV-2 is critical for stopping the current COVID-19 pandemic and preventing future outbreaks. The SARS-CoV-2 main protease (Mpro), a cysteine protease with essential functions in viral replication, has been validated as an effective drug target. Here, we show that Mpro is subject to redox regulation in vitro and reversibly switches between the enzymatically active dimer and the functionally dormant monomer through redox modifications of cystei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…[11] At supraphysiological concentrations of H 2 O 2 , 20 mM, NOS bridges were no longer detected due to over-oxidation. [12] The formation of such a cross-link requires the oxidation of both Cys and Lys residues. Cys residues are broadly known to oxidise through the thiol moiety leading to a wide variety of oxidation products such as the thiyl radical, the disulfide bond or the sulfenic acid under mild oxidation conditions or the sulfinic acid under higher oxidant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[11] At supraphysiological concentrations of H 2 O 2 , 20 mM, NOS bridges were no longer detected due to over-oxidation. [12] The formation of such a cross-link requires the oxidation of both Cys and Lys residues. Cys residues are broadly known to oxidise through the thiol moiety leading to a wide variety of oxidation products such as the thiyl radical, the disulfide bond or the sulfenic acid under mild oxidation conditions or the sulfinic acid under higher oxidant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…9 Further studies have identified the NOS switch in crystal structures across a variety of systems and organisms including SARS-CoV-2, potentially playing an important role in regulation, cellular defense, and replication. 10,11 Moreover, computational insights have also been laid out on exploratory reaction mechanisms of the formation of the NOS bridge. 12 Even though the NOS bridge's chemical identity was clearly shown by protein crystallography at sub-ångstrom resolution, its presence in solution has so far never been directly demonstrated.…”
mentioning
confidence: 99%
“…This causes a reconfiguration of key catalytic residues evoking an increase in enzymatic activity by several orders of magnitude . Further studies have identified the NOS switch in crystal structures across a variety of systems and organisms including SARS-CoV-2, potentially playing an important role in regulation, cellular defense, and replication. , Moreover, computational insights have also been laid out on exploratory reaction mechanisms of the formation of the NOS bridge …”
mentioning
confidence: 99%